Concerning the Lewis acidity of NO+ and NO2/+ as measured by their affinity to selected bases - Cacace, Fulvio (2000)
Recently published theoretical results concerning the NO+ and NO2/+ gas-phase affinities of a few selected molecules, as well as the correlation between the above quantities and the corresponding proton affinities, are examined in the context of the much larger body of experimental and theoretical data already reported in the literature.